Injertos y otras técnicas de propagación del cacao - Somarriba, Eduardo; Astorga Domian, Carlos; Vásquez Morera, Nelly; Cerda Bustillos, Rolando; Orozco Aguilar, Luis; Quesada Chaverri, Francisco (2015)
THEOBROMA CACAO; INJERTO; PROPAGACION VEGETATIVA; MATERIALES DE EXTENSION